LES CONFLITS INTERCOMMUNAUTAIRES EN REPUBLIQUE DEMOCRATIQUE DU CONGO : Essai d’analyse sur les causes - BATOKO, Valentin ETSHIKE (IJRDO - Journal of Social Science and Humanities Research, 2018)
Since the arrival of colonists up to now, the democratic republic of congo faces a bad period enameled by violent conflicts between communities. All these did not come up spontaneously and don’t simply reveal old antagonists that emerge periodically. These tragedies have identifying causes, considerably intensfied by ethnic cleavage intended for marginalization and exclusion to one an other. Briefly, the handling of population by the political leaders through the myth of landwners lies on the effets of the cake that has become very lettle for farmers and breeders, as well as the poverty encountered by the surrounding populagtion and the non-respect of moral values are the basis of those conflicts between communities.